Case Report: Leishmania and HIV Co-Diagnosis: How to Understand Medical History? - Dujardin, Arthur; de La Blanchardière, Arnaud; Dina, Julia; Stefic, Karl; Ravel, Christophe; Bonhomme, Julie; Verdon, Renaud; Fournier, Anna Lucie (Frontiers in Immunology, 2021)
We report a case of a severe visceral leishmaniasis revealing an HIV-1 infection presenting as an acute primary infection. A young French man living in Paris with history of unprotected sex with a recent male partner and recent travel in Greece was admitted in our Infectious Diseases Department, presenting with acute febrile psychotic disorder, and positive HIV-1 serology with high viral load, very low CD4+ T-cells count and a western blot pattern suggesting an acute infection. The psychotic disorder was finally related to hemophagocytic lymphohistiocytosis diagnosed on bone marrow aspiration, supposedly secondary to HIV acute primary infection. The progressive worsening of pancytopenia despite antiretroviral treatment and the persistence of fever, chills and sweat led to the diagnosis of visceral leishmaniasis through bone marrow biopsy and leishmanial serology. He was treated with intravenous liposomal amphotericin B with quick improvement. We discuss the way HIV infection and visceral leishmaniasis may have interact to lead to the clinical presentation of our patient.